PENGARUH EFIKASI DIRI DAN KEMANDIRIAN BELAJAR PESERTA DIDIK SMP TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Vernelli, Rizka Aulyani (Departemen Matematika, 2023)
The effect of Self-Efficacy and Learning Independence of SMP Negeri 25 Padang Students on Mathematics Problem Solving Ability. This study sains to determine the effects of self-efficacy and learning independence of students at SMP Negeri 25 Padang on Mathematical Problem Solving Ability. The research method used is a survey method with quantitative research. This research was conducted at SMP Negeri 25 Padang in class IX in the academic year 2022/2023. Samples were taken using a simple random sampling technique of 120 students. The instruments used are. questionnaires and tests. The data were analyzed first by data analysis test, namely normality test, linearity test, and multicollinearity test. After the data analysis test was met, then the research hypothesis was tested using simple regression analysis techniques. From the results of the study it was found that: (1) there was a significant influence between self-efficacy on mathematical problem-solving abilities; (2) there is a significant influence between. learning independence on mathematical problem solving abilities; (3) there is a significant influence between self-efficacy on learning independence. Keywords – Self-Efficacy, Independent Learning, Problem Solving Ability